Early warning scores in paediatrics: an overview - Chapman,SM; Maconochie,IK (Archives of Disease in Childhood, 2019)
Paediatric Early Warning Scores (PEWS)are used in hospitalised patients to detect physiological deterioration and is being used increasingly throughout healthcare systems with a limited evidence based. There are two versions in general use that can lead to a clinical response, either by triggering an action or by reaching a 'threshold' when graduated responses may occur depending on the value of the score. Most evidence has come from research based on paediatric inpatients in specialist children's hospitals, although the range of research is expanding, taking into account other clinical areas such as paediatric intensive care unit, emergency department and the prehospital setting. Currrently, it is uncertain whether a unified system does deliver benefits in terms of outcomes or financial savings, but it may inform and improve patient communication. PEWS may be an additional tool in context of a patient's specific condition, and future work will include its validation for different conditions, different clinical settings, patient populations and organisational structure. The incorporation of PEWS within the electronic health records may form a keystone of the safe system framework and allow the development of consistent PEWS system to standardise practice.